EFEK MODERASI KEBIJAKAN DIVIDEN DALAM PENGARUH PROFITABILITAS SOLVABILITAS TERHADAP NILAI PERUSAHAAN - Khasanah, Anisatuz Zahroh; Sartika, Farahiyah (Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2022)
This study aims to analyze the effect of Profitability represented by Return on Assets (ROA) and Solvency represented by Debt to Asset Ratio (DAR) on Firm Value Moderated by Dividend Policy of companies listed in the Kompas 100 Index for the 2019-2021 period. This analysis uses multiple linear regression and moderating regression analysis (MRA). The sampling technique used is purposive sampling, as many as 42 samples at the Kompas 100 Index company for the 2019-2021 period. The results showed that profitability (ROA) had a significant effect on firm value, solvency (DAR) had an effect on firm value. Meanwhile, dividend policy is able to moderate or strengthen the influence of profitability on firm value but is unable to moderate the influence of solvency on firm value.